Structural Phase Transition in CdSb + 3 % MnSb Composite at a High Hydrostatic Pressure - R.G. Dzhamamedov; A.Ju. Mollayev; A.V. Kochura; P.V. Abakumov; R.K. Arslanov; S.F. Marenkin; M.B. Dobromyslov (Журнал нано- та електронної фізики)
In CdSb + 3 % MnSb composite, structural properties have been studied, specific resistance ρ and Hall coefficient RH are measured at a high hydrostatic pressure of up to P ≤ 9 GPa. An irreversible structural phase transition is found at barometric dependencies p(P) and RH(P). From our experimental data, barometric dependencies of carrier concentration and their mobility are calculated. On the basis of the heterophase structure – effective medium model, characteristic points and parameters of the phase transition, and also dynamics of variation of the initial phase volume C1 as a function of pressure are computed. The latter dependence is in agreement with the investigation results of Raman scattering before and after application of pressure.